Demographic and population response of the threatened coral Acropora cervicornis (Scleractinia, Acroporidae) to fireworm corallivory - Santiago-Padua, Paola (2023)
Introduction: The fireworm Hermodice carunculata is a widespread polychaete that can prey upon many coral species. However, few studies have examined the effect of fireworm predation on coral demographics during non-outbreak periods.  Objective: To determine whether predation by H. carunculata compromised the growth, survival, and population performance of the threatened coral Acropora cervicornis.  Methods: Nursery-reared coral fragments (n = 99) were fixed to the bottom of Punta Melones reef in the Island Municipality of Culebra, Puerto Rico. Predation activity and its demographic consequences on coral outplants were assessed from December 2020 to August 2022. Susceptibility to predation was compared between colonies collected directly from the reef and those originating from outside sources (e.g., coral nurseries). With the demographic data, simple size-based population matrix models were developed to 1) examine whether fireworm predation led to a significant decline in population growth rate (λ), 2) determine the demographic transition(s) that contribute the most to λ, and 3) determining the demographic transition(s) that accounted for differences in λ when comparing scenarios that considered either only predated colonies or both predated and non-predated outplants.  Results: Predation increased over time, being more frequently observed in the area with the highest topographic relief and on colonies foreign to the study site. Outplants that were partially consumed grew significantly slower than non-predated colonies; however, predation did not threaten their survival. The likelihood of being attacked by the fireworm increased with branching complexity. The estimated λ for a scenario considering only those predated colonies was 0.99, whereas, for a scenario where both predated and non-predated colonies were considered, λ was 0.91. Population growth, under both scenarios, was mainly influenced by the probability of a large colony surviving and remaining at the largest size.  Conclusions: Although predation can negatively impact coral growth, the relatively high survival rate of predated colonies compensates for the adverse effects. Since survival is the demographic transition that contributes most to population growth, it could be concluded that under a non-outbreak scenario, fireworm predation may not be the primary cause of A. cervicornis population decline.